Comparison of D-dimer Levels Based on COVID-19 Severity Degree in Third-trimester Pregnant Women at dr. Doris Sylvanus Hospital - Nurfianto, Sigit; Adnyana, I Gde Hary Eka; Suhanda, Rachmad; Evrillisa, Ghina Alya; Laurentina, Yoriko (Poltekkes Kemenkes Palu, 2024)
Pregnant women are vulnerable to COVID-19 due to the physiological adaptive changes and immunosuppressive state during pregnancy. Various studies on COVID-19 patients have shown the prognostic value of elevated D-dimer. Pregnant women with COVID-19 experience hypercoagulability and hyperfibrinolysis, as indicated by the increased D-dimer levels that exceed normal limits during pregnancy. This study aims to determine the comparison of D-dimer levels based on the COVID-19 severity degree in third-trimester pregnant women at dr. Doris Sylvanus Hospital Palangka Raya. This research is an analytical observational study with a cross-sectional design. It used the medical record data of third-trimester pregnant women confirmed positive for COVID-19 who underwent D-dimer examination at dr. Doris Sylvanus Hospital, Palangka Raya, during November 2020–October 2021, and limited to be generalized to places that has similarity with this hospital. Descriptive analysis in this study used the Kruskal Wallis test and Mann Whitney test. There is a significant difference in D-dimer levels based on the severity of COVID-19 with mild and moderate severity as indicated by the p=0.000 value. In mild and severe severity, the value of p=0.001 means that there is a significant difference, whereas in moderate and severe severity showed a value of p=0.101 which means there was no significant difference. Mild severity has median 1.21, Moderate 2.71 and Severe 4.20. D-dimer and SpO2 data showed non-normally distributed data. It is an important topic to be studied because D-dimer levels can be the parameter for patients with COVID-19 severity status.